MODEL PENGEMBANGAN LOMPAT WARNA DALAM PEMBELAJARAN PENJASORKES UNTUK MENINGKATKAN MOTIVASI GERAK SISWA TUNARUNGU WICARA DI SDLB ABC â€SWADAYAâ€ KENDAL (Department of Physical Education, Sport, Health and Recreation, 2015)
The purpose of this study is to produce a model of learning development that aims to increase motivation for students with hearing and speech impaired movement in SDLB ABC